PENGUATAN MODERASI BERAGAMA MELALUI PEACE EDUCATION GUNA MEWUJUDKAN JURNALISME DAMAI - Sidik Permana; Mursyid Setiawan (Jurnal Soshum Insentif, 2021)
Abstract - Diversity is a necessity that cannot be separated from human life. In order to maintain the harmony of life in this diversity, peace must be fought for by all parties, one of which is through peace education. The goal of peace education is to produce people who are wise and able to position themselves through a process of strengthening moderation. This research is based on Johan Galtung's thoughts with his concept of "peace" and "violence" which is a reference for the creation of resolution and post-conflict. This research uses qualitative methods with literature studies through various reference sources, both from books, journals, official websites, and so on. The implementation of Johan Galtung's thoughts in peace education is expected to foster self-discipline and produce individuals who are not only able to interpret peace, create conflict resolution, are able to position themselves in every problem, but also lead to a transformative and lasting peace, without ignoring the presence of violence that will lead to peace. always present as peace is born. This is what is currently needed, especially for the world of journalism which is closely related to the flow and battle of information. With this peace education, it is hoped that a journalist can make decisions to produce journalistic work that is able to reconcile, be balanced, and even become a solution effort to produce transformation and conflict resolution. Abstrak – Keberagaman merupakan keniscayaan yang tidak bisa dipisahkan dari kehidupan manusia. Guna menjaga keharmonisan hidu dalam keberagaman tersebut, perdamaian harus diperjuangkan semua pihak, salah satunya melalui peace education (pendidikan damai). Tujuan dari peace education melahirkan insan yang bijaksana dan mampu memposisikan diri melalui proses penguatan moderasi. Penelitian ini bertitik tolak pada pemikiran Johan Galtung dengan konsep “peace” dan “violence”-nya yang menjadi rujukan bagi terciptanya resolusi dan pasca konflik. Riset ini menggunakan metode kualitatif dengan studi pustaka melalui berbagai sumber referensi, baik dari buku, jurnal, laman resmi, dan sebagainya. Implementasi pemikiran Johan Galtung dalam peace education ini diharapkan menumbuhkan kebijaksanaan diri dan melahirkan individu yang tidak hanya mampu memaknai kedamaian, menciptakan resolusi konflik, mampu memposisikan diri dalam setiap problematika, tetapi juga membawa ke arah kedamaian yang transformatif dan abadi, tanpa mengabaikan kehadiran kekerasan yang akan selalu hadir seiring perdamaian terlahir. Hal itulah yang saat ini dibutuhkan, terlebih bagi dunia jurnalistik yang erat kaitannya dengan arus dan pertarungan informasi. Dengan peace education ini, diharapkan seorang jurnalis dapat mengambil keputusan untuk menghasilkan karya jurnalistik yang mampu mendamaikan, berimbang, bahkan menjadi upaya solutif untuk menghasilkan transormasi dan resolusi konflik.